Analisis Putusan Nomor. 6/Pid.Sus-Anak/2018/PT Jmb Tentang Sanksi Pidana Terhadap Tindak Pidana Aborsi Perspektif Hukum Positif dan Hukum Islam - Irfan Harmain; Ilham Abdi Prawira; Rizki Zulpadli (IAIN Langsa, 2023)
The rise of abortion often results in pros and cons to the application of sanctions, while the judge's consideration is also determined by the basis or element of the abortion action. This study aims to find out how the application of criminal sanctions to the criminal act of abortion. Then review whether the judge's consideration of the decision case Number: 6 / Pid.Sus-Anak / 2018 / PT. Jmb is based on the principle of justice, the principle of legal certainty and the principle of legal expediency. This research uses normative legal research methods. This study uses primary and secondary sources of legal materials. The techniques used in collecting research data are interviews, observations and documentation. Meanwhile, data analysis from this study was carried out based on descriptive analysis, where data analysis consists of data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the application of criminal sanctions for the criminal act of abortion in the decision of case Number: 6 / Pid.Sus-Anak / 2018 / PT. Jmb is in accordance with applicable regulations, namely based on article 48 of the Criminal Code Jo. article 75 paragraph 2 of Law number 36 of 2009 That the judge in deciding the case has applied / considered the principles of justice, certainty, and legal expediency for the defendant in accordance with the facts of the field.